Empirical investigation of authentic assessment theory: An application in online courses using mimetic simulation created in university learning management ecosystems. Issue 1 (2nd January 2021) - Way, Kïrsten A.; Burrell, Lisa; D'Allura, Louise; Ashford-Rowe, Kevin
Abstract: Authentic assessment has theorised benefits for student outcomes in higher education. More needs to be done, however, to empirically test relationships between the critical elements of authenticity and student outcomes, particularly in online learning environments. In this paper we examine whether an online simulation-based learning and assessment design, developed using the tools and functionality within the available university online ecosystem, has measurable 'authenticity' in a postgraduate course. In addition, we assess whether the simulation is associated with improvements in student learning behaviours and outcomes. We analyse qualitative data from lecturer and student interviews and student work submitted online, as well as data analytics from the learning management system in both control and experimental conditions. Seven critical elements of authentic assessment were identified including new aspects of authenticity relating to simulation-specific affordances (e.g. emotional content, temporal dimensions and unpredictability). Students watched lecture videos and participated in online discussion more frequently in the online simulation than in the control condition and indicated perceived mastery of, and confidence in, the learning outcomes. These findings make important contributions to authentic assessment theory and have practical implications for simulations built in online ecosystems available in higher education.